Solitary metastasis in the internal auditory canal from non-small cell lung carcinoma: A case report - Julie De Boos; Marie Bruyneel; Ionela Bold (Respiratory Medicine Case Reports)
Background: Metastases to the internal auditory canal (IAC) are exceedingly rare. This case report details the case of a patient with a history of locally advanced non-small cell lung carcinoma (NSCLC) who developed a solitary IAC metastasis. Case presentation: A 59-year-old active smoker was initially diagnosed with a locally advanced, unresectable stage IIIA Pancoast tumor (NSCLC, cT4N1M0) and treated with concurrent chemoradiation (cisplatin-pemetrexed) followed by immunotherapy (durvalumab). A subsequent PET CT scan indicated a complete metabolic response. Eighteen months later, the patient presented with rapidly progressing vertigo, left-sided facial palsy, and hearing loss. MRI revealed enhancement on nerves VII and VIII, with no intracranial metastasis or leptomeningeal enhancement. A biopsy via an endoscope-assisted retrosigmoid approach confirmed that it was an NSCLC metastasis. Gamma knife radiosurgery was initiated, resulting in a favorable clinical and radiological response. Discussion: IAC metastases are rare, representing only 0.3%–0.7 % of all lesions in this anatomical space. Lung cancer is a common primary source. Clinically, IAC metastases manifest with acute onset and rapid symptom progression, often mimicking benign conditions. MRI with gadolinium contrast is the imaging modality of choice. Biopsy, though challenging, is sometimes crucial for definitive diagnosis. Gamma knife radiosurgery is a promising treatment, offering potential preservation of hearing and tumor control. Conclusion: This rare case underscores the importance of considering metastatic IAC lesions in patients with a history of malignancy, highlights the feasibility of a biopsy via retrosigmoid approach for diagnosis, and demonstrates the effectiveness of gamma knife radiosurgery.